Ustekinumab trough levels predicting laboratory and endoscopic remission in patients with Crohn’s disease - Hirayama, Hisashi; Morita, Yasuhiro; Imai, Takayuki; Takahashi, Kenichiro; Yoshida, Atsushi; Bamba, Shigeki; Inatomi, Osamu; Andoh, Akira (BMC gastroenterology, 2022)
Backgrounds Optimal concentration of ustekinumab (UST) predicting endoscopic remission has not been fully investigated in Crohn’s disease (CD). We aimed to identify the optimal UST trough levels predicting clinical, laboratory and endoscopic remission in CD patients. Methods Twenty-eight patients with CD were enrolled and investigated (27 patients by enteroscopy and 1 by colonoscopy). The endoscopic activity was assessed using the scoring system that applied the Rutgeerts score to observed intestine. Serum UST trough levels and anti-UST antibodies (AUAs) levels were determined by in-house immunoassays. Results Endoscopic activity was negatively correlated with serum UST trough levels (Spearman’s rank correlation coefficient (ρ) = − 0.66, P = 0.0001) and serum albumin levels (ρ = − 0.60, P = 0.0007). The endoscopic activity was positively and significantly correlated with CRP (ρ = 0.59, P = 0.0009) and ESR (ρ = 0.44, P = 0.033). There was no significant association between the endoscopic score and AUA levels and/or Crohn’s disease activity index (CDAI). Serum UST trough levels and albumin levels were significantly higher in the endoscopic remission group (scores of 0 and 1) than in the non-endoscopic remission group (UST trough, mean 3.3 vs. 1.8 μg/mL). No significant difference was observed in AUAs between the endoscopic remission and non-remission groups. Receiver operation curve (ROC) analysis revealed that the optimal cutoff value of UST trough levels predicting normal CRP and serum albumin levels was 1.7 μg/mL for each, and the optimal cutoff value predicting endoscopic remission was 2.0 μg/mL (AUC: 0.80, 95% CI 0.64–0.96). Conclusion Achievement of endoscopic remission requires higher UST trough levels than required for normalization of CRP and serum albumin levels.